Scores of a web-based version of the seasonal pattern assessment questionnaire in Brazil - Denis Martinez; Roberto Pacheco da Silva; Cristiane Maria Cassol; Gabriel Natan Pires (Clinical and Biomedical Research, 2015)
Introduction: Seasonal affective disorder (SAD) is a proposed mental disorder still controversial. This condition is prevalent in northern latitudes, but few studies have been conducted at locations in the southern hemisphere. It is usually assessed by the Seasonal Pattern Assessment Questionnaire (SPAQ). This study aimed to evaluate, through on-line questionnaire, the hypothesis that, in the Brazilian population, latitude and longitude influence SPAQ scores.